Potential Roles of α-amylase in Alzheimer’s Disease: Biomarker and Drug Target - Chen, Win N.; Tang, Kim San; Yeong, Keng Yoon (Current Neuropharmacology, 2022)
Alzheimer’s disease (AD), the most common form of dementia, is pathologically characterized by the deposition of amyloid-β plaques and the formation of neurofibrillary tangles. In a neurodegenerative brain, glucose metabolism is also impaired and considered as one of the key features in AD patients. The impairment causes a reduction in glucose transporters and the uptake of glucose as well as alterations in the specific activity of glycolytic enzymes. Recently, it has been reported that α-amylase, a polysaccharide-degrading enzyme, is present in the human brain. The enzyme is known to be associated with various diseases such as type 2 diabetes mellitus and hyperamylasaemia. With this information at hand, we hypothesize that α-amylase could have a vital role in the demented brains of AD patients. This review aims to shed insight into the possible link between the expression levels of α-amylase and AD. Lastly, we also cover the diverse role of amylase inhibitors and how they could serve as a therapeutic agent to manage or stop AD progression.
Keywords: alpha-amylase